Kesiapan Penggunaan Teknologi Informasi Pada Pengawasan Internal Penyelenggaraan Pemerintahan Daerah (Studi Pada Inspektorat Kabupaten Sumenep) - Astri Furqani; Rusnani Rusnani (Jayapangus Press, 2021)
Many local governments have implemented information technology-based systems in their business processes such as e-budgeting, e-procurement, electronic licensing and other applications. This phenomenon must be anticipated by the Regional Inspectorate. The use of information technology by the Regional Inspectorate in Internal Supervision of the implementation of Regional government is a necessity in the era of the industrial revolution 4.0. The purpose of this research is to determine the readiness of the Inspectorate of Sumenep Regency in the use of information technology in the internal supervision of the implementation of the regional government of Sumenep Regency. This research uses a qualitative approach with a descriptive type case study method. The informants in the study were four people, namely one structural official and three functional auditors, with a minimum work experience of four years. The process of testing the validity of the data uses triangulation. The data analysis in this study used the Mutula and Brakel models. Based on the results of the analysis using the Mutula-Brakel model with 5 components, there are 2 components that are not fully ready, namely the information readiness for the application of IT under supervision, represented by server availability and insufficient information management guidelines. Server procurement is constrained by refocusing due to the COVID-19 pandemic, but this has been re-budgeted for in 2021. In addition, infrastructure readiness for IT implementation under supervision is not fully adequate